USM SUPER BIKERS HELP PROMOTE USM FOUNDATION TO THE PUBLIC - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 – In an effort to introduce and promote the Universiti Sains Malaysia (USM) Foundation to the public, various programmes have been lined up by the USM Super Bikers group to assist in raising sponsorships, and allowing for more communityuniversity engagement programmes to be carried out.